2022
DOI: 10.1021/acs.energyfuels.2c01145
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Speciation of Naphthenic Acids in Brazilian Crude Oils by Advanced Analytical Techniques

Abstract: The characterization of naphthenic acids (NAs) in petroleum samples has received particular attention and is still an analytical challenge as a result of the complexity of the matrix. This study aims to individually and comprehensively characterize NAs in real Brazilian crude oils by Orbitrap high-resolution mass spectrometry (Orbitrap− HRMS) and comprehensive two-dimensional gas chromatography with time-of-flight mass spectrometry (GC × GC−TOFMS). Linear, branched, and cyclic carboxylic acids were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…1,2 Crude oils that have a total acid number (TAN) over 0.5 are labeled as acidic. 3 TAN is measured by titrating 1 g of crude oil with KOH to assess the required milligrams of KOH. 4 From the refining point of view, high TAN crudes are cheaper to purchase, hence considered as opportunity crudes that generate high refining margins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Crude oils that have a total acid number (TAN) over 0.5 are labeled as acidic. 3 TAN is measured by titrating 1 g of crude oil with KOH to assess the required milligrams of KOH. 4 From the refining point of view, high TAN crudes are cheaper to purchase, hence considered as opportunity crudes that generate high refining margins.…”
Section: Introductionmentioning
confidence: 99%
“…To provide an additional supply for the ever-growing fuel demand, high acid crude oils are considered as a good option, to be used as raw feedstocks in crude oil refineries. , Crude oils that have a total acid number (TAN) over 0.5 are labeled as acidic . TAN is measured by titrating 1 g of crude oil with KOH to assess the required milligrams of KOH .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have demonstrated the analysis of NAs utilizing gas chromatography (GC) [29][30][31][32][33][34], liquid chromatography [5,34,35], and direct MS analysis [36,37]. On the other hand, only a few studies involving the analysis of NAs by CE can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%